Historical Dictionary of Ancient India - Roy, Kumkum (Rowman & Littlefield Publishers, 2008)
India's history and culture is ancient and dynamic, spanning back to the beginning of human civilization. Beginning with a mysterious culture along the Indus River and in farming communities in the southern lands of India, the history of India is punctuated by constant integration with migrating peoples and with the diverse cultures that surround the country. Placed in the center of Asia, history in India is a crossroads of cultures from China to Europe, as well as the most significant Asian connection with the cultures of Africa. The Historical Dictionary of Ancient India provides information ranging from the earliest Paleolithic cultures in the Indian subcontinent to 1000 CE. The ancient history of this country is related in this book through a chronology, an introductory essay, a bibliography, and hundreds of cross-referenced dictionary entries on rulers, bureaucrats, ancient societies, religion, gods, and philosophical ideas.